ЕСТЕСТВЕННОНАУЧНАЯ ГРАМОТНОСТЬ И ЕЁ РОЛЬ В СИСТЕМЕ НАЧАЛЬНОГО ОБРАЗОВАНИЯ - Аманкличев, И.Б. (SCIENCE and SOCIETY, 2025)
This article explores the content and essence of the concept of scientific literacy, presenting it as a multifaceted process. It provides a theoretical and scientific justification for the importance of developing scientific literacy among primary school students. The role of SCIENCE natural sciences, in enhancing scientific literacy among general secondary school students is highlighted. The article also proposes recommendations for the professional preparation of future primary school teachers to teach natural sciences effectively.